Managing an arts faculty in a disruptive technology environment - Mat Daud, Nuraihan (2019)
Technological advancement has impacted on the way a faculty is run. In many ways, it has made management more effective provided we know how to take advantage of its existence. Systems such as student management system, learning management system, admission system are among those that are needed in order to run a university effectively. Apart from these systems, social networks are increasingly used in managing a faculty. The fact is machines will continue to take over our jobs especially those that can be automated. Where teaching is concerned the modern teachers are expected to go for active approaches and to integrate the technology into their teaching. Preparing students to face the 4th and 5th Industrial Revolutions would demand more than the traditional in-class teacher-centred teaching approach. A curriculum that can produce independent learners may help to prepare our learners for the unknown future and the rapidly changing society. There is a need for us to come up with a more flexible programme that aims at producing students who can adapt to changes that are taking place in the society. This paper discusses some of the changes that have taken place with the advancement of technology in managing an Arts Faculty. Initiatives taken to keep abreast with the latest development of technology will also be shared.